An Investigation into the Vancomycin Concentration in the Cerebrospinal Fluid Due to Vancomycin Intraventricular Administration in Newborns: A Study of 13 Cases. Issue 22 (June 2015) - Matsunaga, Nobuaki; Hisata, Ken; Shimizu, Toshiaki
Abstract : Abstract: Treatment against shunt infection by transvenous antimicrobial treatment is difficult, with a high risk of relapse. Consequently, to maintain a sufficient cerebrospinal fluid (CSF) concentration, intraventricular administration is utilized in combination with the transvenous administration of vancomycin (VCM). Few studies have so far investigated the optimum administration dose for newborns and the concentration in the CSF. Therefore, we chronologically measured the VCM concentration in the CSF after VCM intraventricular administration in newborns and attempted to elucidate the optimum administration method. The participants consisted of newborns admitted to Juntendo University Neonatal intensive care unit from March 2007 to June 2011 who underwent interventricular shunting placement. VCM was intraventricularly administered to 10 patients for a total of 13 cases. The CSF concentration of VCM was chronologically measured at 12 to 120 hours following the intraventricular administration of VCM. The intraventricular administration groups with VCM of 20 (n = 6) and 10 mg (n = 2) had a high concentration in the CSF at 24 hours following administration (95–168 mg/L), with the concentration remaining high at 72 hours (13.2–72 mg/L). At the same time, in the 5 mg group (n = 5), the concentration in the CSF 24 hours following VCM administration was sufficiently maintained (33.2–62.9 mg/L), with a sufficient trough concentration still maintained at 72 hours (11.7–16.5 mg/L). The concentration in the CSF is prolonged in newborns, thus allowing a sufficient therapeutic range to be maintained even at an intraventricular administration of 5 mg. It is therefore believed that the monitoring of the CSF is very important regarding the administration interval because the VCM concentration in the CSF differs depending on the case.